2019
DOI: 10.3389/fcimb.2019.00003
|View full text |Cite
|
Sign up to set email alerts
|

Human Tick-Borne Diseases in Australia

Abstract: There are 17 human-biting ticks known in Australia. The bites of Ixodes holocyclus, Ornithodoros capensis, and Ornithodoros gurneyi can cause paralysis, inflammation, and severe local and systemic reactions in humans, respectively. Six ticks, including Amblyomma triguttatum, Bothriocroton hydrosauri, Haemaphysalis novaeguineae, Ixodes cornuatus, Ixodes holocyclus, and Ixodes tasmani may transmit Coxiella burnetii, Rickettsia australis, Rickettsia honei, or Rickettsia honei subsp. marmionii. These bacterial pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 103 publications
(130 reference statements)
0
34
0
Order By: Relevance
“…In Asia, Borrelia burgdorferi infection has been reported in countries including China, Korea, Japan, Indonesia, and Nepal and in eastern Turkey (Jaenson and Lindgren, 2011;Heinz et al, 2015). Beside the above-mentioned areas, cases were reported in more tropical locales, and LD may exist in Australia (Dehhaghi et al, 2019).…”
Section: Epidemiologymentioning
confidence: 99%
“…In Asia, Borrelia burgdorferi infection has been reported in countries including China, Korea, Japan, Indonesia, and Nepal and in eastern Turkey (Jaenson and Lindgren, 2011;Heinz et al, 2015). Beside the above-mentioned areas, cases were reported in more tropical locales, and LD may exist in Australia (Dehhaghi et al, 2019).…”
Section: Epidemiologymentioning
confidence: 99%
“…The expression of Evasins by diverse tick species suggests that they play important roles in promoting tick blood-feeding and survival. Considering that ticks are vectors for viral and bacterial pathogens in humans and both domestic and wild animals [59], it will be important to assess the contributions of Evasins to the spread of infectious diseases and to examine their potential as targets for tick control strategies such as vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The infections transmitted by ticks can be passive, such as from pathogens like poxviruses or apicomplexa present in blood on the tick hypostome or regurgitated during feeding (Tuppurainen et al, 2011; Hammer et al, 2016), and/or active when ticks are vectors for pathogens. Ticks can transmit bacteria of the genera Borrelia , Anaplasma, Rickettsia, Francisella , and others; protozoan parasites of the genus Babesia ; and several viruses, with tick-borne encephalitis virus a major tick-transmitted viral pathogen in humans (Swanson et al, 2006; Coipan et al, 2013; Berggoetz et al, 2014; Jahfari et al, 2016; Kazimirova et al, 2017; Dehhaghi et al, 2019). Early works on tick saliva (Wikel, 1982; Ribeiro et al, 1985) showed that ticks actively modulate and/or inhibit host defense mechanisms, thus enabling the tick to complete its blood meal and facilitate pathogen transmission, as reviewed elsewhere (Francischetti et al, 2009; Wikel, 2013; Kotal et al, 2015).…”
Section: Tick Salivary Secretions and Tick-host-pathogen Interactionsmentioning
confidence: 99%